Implementasi Model Pembelajaran CORE ditinjau dari Prestasi Belajar Kognitif - Nasrulloh, Muhammad Farid; Indrianah, Mei; Umardiyah, Fitri; Sodiq Maksum, Mohammad Jafar (Universitas KH. A. Wahab Hasbullah, 2022)
Problem related to low learning achievement are on of the problems that need to be solved through learning. One of the elements that affect the learning process is the application of the learning models. This research aims to determine whether the CORE learning model can improve mathematics (cognitive) learning achievement. The research methode used is quasi-experimental research with the type of Pre-Experimental Design type One Group Pretest-posttest design. Students of class VIII SMP AL Hikmah Balongrejo become the sample in this research. Data collection thecniques used interviews, valid questionnaires, and learning achievement tests. While the research instruments are pretest and posttest. The data analysis technique used validity test, reliability test, normality test, and paired sample t-test. The result of the study obtained a significant level of 0,000 < 0,05. So it can be concluded the CORE learning model (connecting, organizing, reflecting, extending) can improve learning achievement (cognitive) mathematics.